2016
DOI: 10.1093/jee/tow028
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism and Optimization ofHyposoter didymator(Hymenoptera: Ichneumonidae) Rearing onSpodoptera littoralisandHelicoverpa armigera(Lepidoptera: Noctuidae)

Abstract: This study was carried out to improve the rearing methods of endoparasiteHyposoter didymator(Thunberg) for biological control release. The growth and the development ofH. didymatoron the first, second, and third instars ofSpodoptera littoralis(Boisduval) andHelicoverpa armigera(Hübner) under laboratory conditions were investigated. Results indicated thatS. littoraliswas a suitable host for the rearing of H. didymator The development time of the parasite on the second instar of both hosts was almost the same (∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Moreover, the reproductive potential of H. didymator females, over 3 days, was not affected by direct applications of the fungus on parasitoid adults, even at high conidial concentrations (10 7 and 10 8 conidia ml −1 ), as no significant differences in S. littoralis parasitization were scored during this time for any treatment (Table ). As the most productive copulation/egg‐laying period for H. didymator females and males is 36 h after emergence, our results show that fungus‐treated H. didymator females would have plenty of time to parasitize S. littoralis larvae before being killed by the fungus (≈ 4 days after treatment), even if they were inoculated as soon as they emerged. It is worth stressing that direct contact between the fungus and the parasitoid represents the worst‐case scenario under field conditions and could be prevented, or at least reduced, if fungus is applied after parasitization.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Moreover, the reproductive potential of H. didymator females, over 3 days, was not affected by direct applications of the fungus on parasitoid adults, even at high conidial concentrations (10 7 and 10 8 conidia ml −1 ), as no significant differences in S. littoralis parasitization were scored during this time for any treatment (Table ). As the most productive copulation/egg‐laying period for H. didymator females and males is 36 h after emergence, our results show that fungus‐treated H. didymator females would have plenty of time to parasitize S. littoralis larvae before being killed by the fungus (≈ 4 days after treatment), even if they were inoculated as soon as they emerged. It is worth stressing that direct contact between the fungus and the parasitoid represents the worst‐case scenario under field conditions and could be prevented, or at least reduced, if fungus is applied after parasitization.…”
Section: Discussionmentioning
confidence: 82%
“…That led us to think that the most crucial factor for the parasitoid, and the reason why a lower parasitization was recorded the first day both in the EFP24 and P24 treatments, was the larval instar of the host. It has been shown that H. didymator only parasitizes second (L2) or third (L3) instar S. littoralis larvae . Earlier and later larval stages are considered as low‐quality hosts because they provide few nutrients and have strong immune responses that prevent parasitoid development .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different biological agents such as the entomopathogenic fungi (Ahmed & El‐Katatny, ), entomopathogenic nematodes (Atwa, ; Shairra & Noah, ), viruses (Jones, Moawad, McKinley, & Grzywacz, ) and parasitoids (Depalo, Marchetti, Baronio, Martini, & Dindo, ; Hatem, Shawer, & Vargas‐Osuna, ; Vojtech, Meissle, & Poppy, ) have proven effective against S. littoralis . During surveys of amaranth lepidopteran parasitoids in central Kenya, a new species of Cotesia named Cotesia icipe Fernandez‐Triana & Fiaboe was frequently found parasitizing S. littoralis larvae (Fiaboe, Fernández‐Triana, Nyamu, & Agbodzavu, ).…”
Section: Introductionmentioning
confidence: 99%